THE EFFECT OF FREQUENCY ON THE ELASTIC PROPERTIES OF MATERIALS - Maiyena, Sri; Ayop, Shahrul Kadri; Daud, Anis Nazihah Mat (EduFisika: Jurnal Pendidikan Fisika, 2024)
The elastic properties measurement of materials is important to determine their potential application in industries. Hence, the effect of frequency on the elastic properties is crucial in estimating the material's behavior with the change of frequency. Thus, this study was conducted to determine the effect of frequency on the elastic properties of materials. Five parameters of elastic materials were found in this study: bulk modulus, shear modulus, longitudinal modulus, Young's modulus, and lame constant. The elastic properties of three samples; stainless steel, aluminium and PMMA were measured for 2.25 MHz, 5 MHz and 10 MHz frequency. The method used is non-destructive testing using pulse-echo ultrasound techniques. The findings indicated that the longitudinal modulus, Young's modulus, shear modulus, bulk modulus, and lame constant of all samples are constant as the frequency increased from 2.25 MHz to 10 MHz. In conclusion, the elastic properties of a material are independent to the change of frequency.